1979
DOI: 10.2307/2043137
|View full text |Cite
|
Sign up to set email alerts
|

Free Completely Distributive Lattices

Abstract: Abstract. We show that the usual construction of the free distributive lattice on n generators generalizes to an arbitrary quantity of generators and actually yields a free completely distributive lattice. Furthermore, for an infinite number of generators the cardinality of the corresponding free completely distributive lattice is exactly that of the power set of the power set of the set of generators. . For a finite set, G, of n generators it is well-known that the free distributive lattice over « generators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…A more concrete construction of free objects in CABA can be given utilizing the theory of canonical extensions. It is well known that free objects over any set exist in the category of complete and completely distributive lattices (see Markowski [Mar79] and Dwinger [Dwi81, Thm. 4.2]).…”
Section: Thomason Dualitymentioning
confidence: 99%
“…A more concrete construction of free objects in CABA can be given utilizing the theory of canonical extensions. It is well known that free objects over any set exist in the category of complete and completely distributive lattices (see Markowski [Mar79] and Dwinger [Dwi81, Thm. 4.2]).…”
Section: Thomason Dualitymentioning
confidence: 99%
“…In [28] it is shown that the category Ω-CD is monadic over Set, hence a(n infinitary) variety [21]. In particular, the free completely distributive Ω-category over a set A is Í(dA) [2,38], similarly to the ordered case [22].…”
Section: Completely Distributive Quantale Enriched Categoriesmentioning
confidence: 99%
“…Algebras for the monad A are completely distributive lattices [27]. The sets of sets in A(X) can be seen as DNF formulae over elements of X, where the outer powerset is disjunctive and the inner one is conjunctive.…”
Section: Examplesmentioning
confidence: 99%